Thermophysical, rheological and tribological properties of palm oil with hybrid CuO/MWCNT additive nanoparticles as cutting fluid on CNC machining - Puspitasari, Poppy; Permanasari, Avita Ayu; Hidayat Syah Lubis, Abdul Munir; Ardiansyah, Muhammad Z.; Pramono, Diki Dwi; Abdullah, Muhammad Ilman Hakimi Chua; Chua Abdullah, Muhammad Ilman Hakimi (Malaysian Tribology Society, 2025)
Biolubricant has abundant availability, non-toxic, and environmentally This study aims to analyse the performance of palm oil-based coolant with CuO/MWCNT nanomaterial additives in the CNC milling machining process on thermophysical, rheological and tribological properties including surface roughness, wear debris morphology, and tool wear compared with machining results using commercial coolant. The addition of CuO, MWCNT and hybrid nanoparticle additives to palm oil resulted in an increase in density, thermal conductivity and viscosity, and had good stability up to 20 days. The rheology of palm oil with CuO, MWCNT and hybrid nanoparticle additives has newtonian fluid behavior at temperatures 40ºC and 100ºC. The results of palm oil with CuO/MWCNT nanomaterial hybrid additives as a CNC machining coolant influence improving lubrication properties. The performance of palm oil with MWCNT additive as a CNC machining cutting fluid produces the lowest surface roughness and tool wear, and produces chips with smooth morphology, and silver chip colour. It is concluded that palm oil with MWCNT additive has the best tribological and wear resistance test results among commercial cutting fluids or other samples, so it has the potential to be used in industry to replace commercial mineral oil-based cutting fluids.